Involvement of Corticotropin-Releasing Factor and Receptors in Immune Cells in Irritable Bowel Syndrome - Chatoo, Mahanand; Li, Yi; Ma, Zhiqiang; Coote, John; Du, Jizeng; Chen, Xuequn (Frontiers in Endocrinology, 2018)
Irritable bowel syndrome (IBS) is a common functional gastrointestinal disorder defined by Rome IV criteria as pain in the lower abdominal region, which is associated with altered bowel habit or defecation. The underlying mechanism of IBS is not completely understood. IBS seems to be a product of interactions between various factors with genetics, dietary/intestinal microbiota, low-grade inflammation and stress playing a key role in the pathogenesis of this disease. The crosstalk between the immune system and stress in IBS mechanism is increasingly recognized. CRF, a major mediator in the stress response is involved in altered function in GI, including inflammatory processes, colonic transit time, contractile activity, defecation pattern, pain threshold, mucosal secretory function and barrier functions. This mini review focuses on the recently establish local GI-CRF system, its involvement in modulating the immune response in IBS, and summarizes current IBS animal models and mapping of CRF, CRFR1, and CRFR2 expression in colon tissues. CRF and receptors might be a key molecule involving the immune and movement function via brain-gut axis in IBS.